Reactions to Counterstereotypic Behavior The Role of Backlash in Cultural Stereotype Maintenance. [article]. - Rudman, Laurie, A.
Social and economic sanctions for counterstereotypical behavior have beenterm the backlash effect (l. A. Rudman 1998). The authors present a model of the role backlash in cultural stereotype maintenance from the standpoint of both perceivers and actors. In experiments 1and 2, participants lost a competition to either atypical or typical men or women and subsequently showed greater tendency to sabotage deviants. Moreover, undermining deviants was associated with increased self-esteem, suggesting that backlash rewards perceivers psychologically. Experiment 3 showed that gender deviants who feared backlash resorted to strategies designed to avoid it. (e. g., hiding, deception, and gender comformity). Further, perceivers who sabotageddeviants (Experiment 2) or deviants who hid their atypicality(Experiment 3) estimated greater stereotyping on the part of future perceivers, in the support of the model's presumed role for backlash in stereotype maintenance. The implications of the findings for cultural stereotypes are discussed. -- (from the author)